Teaching English Language and Civic Education in the Era of Artificial Intelligence in Kaduna State, Nigeria: A Teacher's Perspective - Uthman Shehu Lawal; Zulai Muhammad Rabiu; Abu Bakar Rabiu; Zohaib Hassan Sain; Rozanah Katrina Herda (Prominent, 2026)
The integration of artificial intelligence (AI) into education has transformed teaching and learning globally, presenting both opportunities and challenges for educators. This study examined the perspectives of English language and civic education teachers in Kaduna State, Nigeria regarding the implementation of AI in their teaching practices. A descriptive survey research design using a quantitative approach was employed, with a population comprising English language and social studies teachers in Kaduna and Zaria metropolitan areas. A sample of 400 teachers was selected using stratified random sampling. Data were collected using structured questionnaires and interview guides, while the analysis employed descriptive statistics and Pearson Product Moment Correlation (PPMC) with regression analysis. The findings revealed that 78% of the teachers acknowledged the potential of AI to enhance English language instruction, while 65% expressed concerns about its impact on traditional civic education delivery. This study found significant relationships between teachers' digital literacy levels and their acceptance of AI integration (r = 0.67, p < 0.05). The results indicate that teachers with higher educational qualifications showed greater readiness to adopt AI tools in language and civic education. This study recommends comprehensive teacher training programs, infrastructure development, and policy frameworks to support effective AI integration in Kaduna State's educational system. Keywords: artificial intelligence, civic education, english language, teacher perspectives